A lead(II) ion selective electrode via a metal complex of poly(hydroxamic acid) - Anuar, K.; Hamdan, S. (1992)
A new lead(II) electrode has been constructed with poly(hydroxamic acid) (PHXA) as the active material and silicone rubber as the supporting material. The electrode gave near Nerstian response over the concentration range 4 × 10-5-1 × 10-2M lead(II). The detection limit of the electrode is approximately 4 × 10-6M and the electrode works well in the pH range 4.5-6.0. The response time was 50-120 sec over the whole concentration range and the electrode has a working life of at least 4 weeks. Iron(III) severely poisoned the electrode membrane. Nickel(II) and mercury(II) gave very strong interference compared to copper(II), silver(I), cobalt(II), sodium(I), potassium(I), zinc(II) and cadmium(II) which gave some or little interference. Values determined with atomic absorption (AAS) and a commercial lead(II) electrode were in good agreement with those measured with the lead(II) electrode reported here. © 1992.